2020
DOI: 10.3390/vaccines8010113
|View full text |Cite
|
Sign up to set email alerts
|

Low-Energy Electron Irradiation Efficiently Inactivates the Gram-Negative Pathogen Rodentibacter pneumotropicus—A New Method for the Generation of Bacterial Vaccines with Increased Efficacy

Abstract: Bacterial pathogens cause severe infections worldwide in livestock and in humans, and antibiotic resistance further increases the importance of prophylactic vaccines. Inactivated bacterial vaccines (bacterins) are usually produced via incubation of the pathogen with chemicals such as formaldehyde, which is time consuming and may cause loss of immunogenicity due to the modification of structural components. We evaluated low-energy electron irradiation (LEEI) as an alternative method to generate a bacterin. Rode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
(37 reference statements)
1
11
0
Order By: Relevance
“…Consequently, irradiated viruses or bacteria are highly efficient as vaccines against a variety of human or animal infections, and the technology can be used to inactivate pathogens in various biological samples [9][10][11] . There are several advantages over chemical inactivation (currently the only way to produce inactivated vaccines), including the lack of toxic chemicals like formaldehyde, high reproducibility, high conservation of antigenic content and short reaction time 3,9,[12][13][14] .…”
Section: High Concentrations Of Viruses (Influenza Zika Virus and Rementioning
confidence: 99%
“…Consequently, irradiated viruses or bacteria are highly efficient as vaccines against a variety of human or animal infections, and the technology can be used to inactivate pathogens in various biological samples [9][10][11] . There are several advantages over chemical inactivation (currently the only way to produce inactivated vaccines), including the lack of toxic chemicals like formaldehyde, high reproducibility, high conservation of antigenic content and short reaction time 3,9,[12][13][14] .…”
Section: High Concentrations Of Viruses (Influenza Zika Virus and Rementioning
confidence: 99%
“…The curve takes a step down when the chickens were dead. volumes within a short time via damage of nucleic acid (11). Several previous reports have suggested that nucleic acids rather than proteins are the primary targets of gamma irradiation to inactivate microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Gamma irradiation has been used extensively as an alternative inactivation method of pathogens because of its high penetrability, which allows bacterial inactivation in large volumes within a short time via damage of nucleic acid ( 11 ). Several previous reports have suggested that nucleic acids rather than proteins are the primary targets of gamma irradiation to inactivate microorganisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in our laboratories have shown that bacterial cells when inactivated retain their metabolism for specific periods of time in a state termed, Metabolically Active yet Non-culturable (MAyNC) ( 4 ). This technology is used commercially for different applications ( 2 , 3 ), but its use for pathogen inactivation in pharmaceutical development is relatively new. High energy eBeam (HEEB) equipment are bulky and require large concrete structures and, therefore, often difficult to incorporate into existing production lines.…”
Section: Introductionmentioning
confidence: 99%